2021
DOI: 10.3389/fonc.2021.632231
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib in the Management of Pediatric Patients With Philadelphia Chromosome-Positive Acute Lymphoblastic Leukemia

Abstract: Acute leukemia is the most common cancer in childhood; in particular, acute lymphoblastic leukemia (ALL) represents roughly up to 80% of all cases of acute leukemias in children. Survival of children with ALL has dramatically improved over the last few decades, and is now over 90% (versus 40% of adult patients) in developed countries, except for in infants (i.e., children < 1 year), where no significant improvement was registered. Philadelphia positive ALL (Ph+ALL) accounts for around 3% of cases of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Of note, we do not have infant patients in the analysis of this study. Finally, BCR::ABL1 translocation is associated with poor prognosis; this encodes a tyrosine kinase, which is considered a pathogenetic driver that can be therapeutically targeted ( 38 ), and so, fortunately, treatment with tyrosine kinase (TK) inhibitors has improved the overall survival of patients with this rearrangement ( 39 ). In this study, BCR::ABL1p 190 translocation wasentified in 3.6% of the patients and showed low DFS than the other fusion genes, similar to other studies ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we do not have infant patients in the analysis of this study. Finally, BCR::ABL1 translocation is associated with poor prognosis; this encodes a tyrosine kinase, which is considered a pathogenetic driver that can be therapeutically targeted ( 38 ), and so, fortunately, treatment with tyrosine kinase (TK) inhibitors has improved the overall survival of patients with this rearrangement ( 39 ). In this study, BCR::ABL1p 190 translocation wasentified in 3.6% of the patients and showed low DFS than the other fusion genes, similar to other studies ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of dasatinib with dexamethasone best inhibited the activated signaling in resistant cells. Dasatinib is used in combination with standard chemotherapy for patients with ABL alterations (Philadelphia positive 50 or Ph-like BCP-ALL 51 ). Several studies have recently investigated the possibility of using dasatinib to target pre-BCR + leukemia with or without ABL alterations 52 , testing it either alone or in combination with small molecules disrupting CREB-binding protein (CBP) 53 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…It has inhibiting potency due to its association with non-BCR/ABL kinases. Clinical trials proved the effectiveness and safety of Dasatinib combined with traditional chemotherapy in ALL [ 4 ]. Clinical studies of the third generation of TKIs (Ponatinib) have also shown potential, but further tests with accurate dose findings are required [ 5 ].…”
Section: Acute Lymphoblastic Leukemia (All)mentioning
confidence: 99%